1991
DOI: 10.1073/pnas.88.11.4946
|View full text |Cite
|
Sign up to set email alerts
|

Iron-independent induction of ferritin H chain by tumor necrosis factor.

Abstract: Iron increases the synthesis of the ironstorage protein, ferritin, largely by promoting translation of preexisting mRNAs for both the H and L ferritin isoforms (H,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
143
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(155 citation statements)
references
References 37 publications
9
143
0
3
Order By: Relevance
“…In mammals, ferritin genes are regulated in glioma cells by insulin (Yokomori et al, 1991), in thyroid cells by thyrotropin and C A M P (Chazenbalk et al, 1990), in the pancreatic insulin cells by glucose (MacDonald et al, 1994), in adipocytes and muscle cells by tumor necrosis factor a (Miller et al, 1991), and in monocytes by tumor necrosis factor a and interferon y (Fahmy and Young, 1993). These examples underline the observation that ferritin is regulated at the transcriptional level when it is involved in differentiation or developmental processes (Theil, 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, ferritin genes are regulated in glioma cells by insulin (Yokomori et al, 1991), in thyroid cells by thyrotropin and C A M P (Chazenbalk et al, 1990), in the pancreatic insulin cells by glucose (MacDonald et al, 1994), in adipocytes and muscle cells by tumor necrosis factor a (Miller et al, 1991), and in monocytes by tumor necrosis factor a and interferon y (Fahmy and Young, 1993). These examples underline the observation that ferritin is regulated at the transcriptional level when it is involved in differentiation or developmental processes (Theil, 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, others and we demonstrated that overexpression of ferritin H is cytoprotective against oxidative stress (Epsztejn et al, 1999;Cozzi et al, 2000;Orino et al, 2001;Pham et al, 2004). Furthermore, the ferritin H gene, but not ferritin L gene, was identified as a TNF-response gene (Torti et al, 1988;Miller et al, 1991) through activation of NF-kB (Kwak et al, 1995), and very recently NF-kBmediated induction of ferritin H is an essential mediator of the antioxidant and cytoprotective activities against TNF-induced apoptosis (Pham et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ferritin synthesis is regulated at both transcriptional and translational levels (Torti and Torti, 2002). A preferential induction of the H subunit than the L subunit of the ferritin gene was frequently observed in response to environmental and intracellular signals during inflammation (Torti et al, 1988;Miller et al, 1991;Tsuji et al, 1991;Kwak et al, 1995), and differentiation (Chou et al, 1986;Beaumont et al, 1987Beaumont et al, , 1994 in an iron-independent manner. Alterations in the subunit composition of the ferritins have a potential to alter intracellular iron balance because there are functional differences between the H and L subunits of ferritin; the ferritin heavy chain (ferritin H) subunit has ferroxidase activity that oxidizes ferrous iron to ferric iron, while the ferritin L subunit lacks the ferroxidase center but contributes to stabilization of assembled ferritin proteins (Levi et al, , 1994Santambrogio et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] A possible link between TNF-␣ and HHC has been hypothesized on the basis of the observation that TNF-␣ release from lipopolysaccharide (LPS)-stimulated monocytes from patients with HHC was lower than in monocytes from controls, and it was suggested that this could account for the low iron content in monocyte-macrophage cells from patients with HHC. [26][27][28] The aim of this study was to establish whether TNF-␣ plays a role in the phenotypic expression of HHC. To achieve this aim, we studied TNF-␣ release from macrophages from patients with HHC typed for HFE gene mutations, the prevalence of TNF-␣ polymorphism at positions 238 and 308, and the relation between TNF-␣ polymorphism and clinical expression of HHC.…”
Section: Introductionmentioning
confidence: 99%